The Values of Sultan Alauddin's Relevance to The Development of Civilization Campus of Universitas Islam Negeri Alauddin Makassar - Mustari, Mustari; Said, Nurhidayat Muhammad; B, Jalaluddin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2023)
This research underlines that giving a university the identity of a local character is an effort at reproducing the subject's value in establishing a more civilized campus and community. Universitas Islam Negeri Alauddin Makassar is one of the Islamic universities bearing the name of Sultan Alauddin, the 14th King of Gowa and the first Muslim convert in the Kingdom of Gowa that endeavors to develop an inclusive and socialist Islamic civilization by way of his approach to learning. Hence, this research is aimed to retrace Sultan Alauddin's worldview, both as a warrior for his country in Gowa and as a fighter for Islam's teachings as the purest belief beyond his predecessors' teachings. Sultan Alauddin's worldview has created a civilization space for Universitas Islam Negeri Alauddin Makassar, which is known throughout Eastern Indonesia. This research seeks to comprehend Sultan Alauddin's major ideals as a reference instrument in order to construct a campus culture capable of dealing with the dynamics of contemporary development. A literature review is used as a data source in this research, which is then studied in four stages: heuristics, critique, interpretation, and historiography. Consistent with the result of this research, Sultan Alauddin Makassar's worldview prioritizes five characteristics: open-mindedness, receptivity, adaptiveness, rationality, and critical thinking. The reflection of this worldview has given rise to a civilization capable of answering numerous societal challenges and forming a critical viewpoint on problematical what is known as the